2017
DOI: 10.1016/j.jfca.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Folates in quinoa ( Chenopodium quinoa ), amaranth ( Amaranthus sp.) and buckwheat ( Fagopyrum esculentum ): Influence of cooking and malting

Abstract: Effects of processing on the contents of five folate vitamers in quinoa, amaranth and buckwheat were analyzed using a trienzymatic extraction method followed by LC-MS/MS. Total folate (TF) content, corresponding to the sum of folic acid (FA), 5-methyltetrahydrofolate (5-MTHF) and 10formyltetrahydrofolate (10-CHOTHF) expressed as folic acid equivalent, in raw quinoa, amaranth and buckwheat were 309±8.07, 228±24.2 and 153±12.4 µg/100 g dw, respectively, being dominantly 5-MTHF. Boiling and steaming reduced the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 32 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…The SP folic acid content is 3.8 times higher compared with OR sourdough and this is in agreement with [69] who reported that L. plantarum CRL 2107 + L. plantarum CRL 1964 strains are able to improve folic acid content during quinoa flour fermentation. The capacity of Lactobacillus strains to produce folic acid during fermentation is supported by a large body of literature [70][71][72][73][74]. Likewise, [55] reported that through fermentation of cereal based foods, the folate content could increase up to 700%.…”
Section: Sp and Or Folic Acid Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The SP folic acid content is 3.8 times higher compared with OR sourdough and this is in agreement with [69] who reported that L. plantarum CRL 2107 + L. plantarum CRL 1964 strains are able to improve folic acid content during quinoa flour fermentation. The capacity of Lactobacillus strains to produce folic acid during fermentation is supported by a large body of literature [70][71][72][73][74]. Likewise, [55] reported that through fermentation of cereal based foods, the folate content could increase up to 700%.…”
Section: Sp and Or Folic Acid Contentmentioning
confidence: 99%
“…Folic acid ((μg/100 g) f.w. The capacity of Lactobacillus strains to produce folic acid during fermentation is supported by a large body of literature [70][71][72][73][74]. Likewise, [55] reported that through fermentation of cereal based foods, the folate content could increase up to 700%.…”
Section: Qp and Qq Macro And Microelements Contentmentioning
confidence: 99%
“…22 Germination treatment further enriched total folate levels in quinoa with 5-CH 3 -THF to be identified as the major folate derivative. 23 Our previous research found that the level of 5-CH 3 -THF in 6-day-old quinoa sprouts was 50−80 times higher than that of quinoa seeds. 20 However, the molecular mechanisms involved in the surge of folate during the germination of quinoa seeds have not been well understood.…”
Section: Introductionmentioning
confidence: 92%
“…Folate is known to be an unstable vitamin, with 35-70% loss due to storage and processing [6]. Motta et al [73] investigated the effects of processing on folate content in amaranth. The authors found that boiling and steaming reduced total folate content by 58% and 22%, respectively.…”
Section: Folatementioning
confidence: 99%
“…5-CHO-H 4 , which is considered rather stable, is also the predominant vitamer in cereal products [71]. Motta et al [73] identified 5-CH 3 -H 4 as the most abundant form of folate in amaranth, quinoa, and buckwheat. However, the authors detected only three folate vitamers.…”
Section: Folatementioning
confidence: 99%